Testing the concept of green infrastructure at the Baltic Sea scale to support an ecosystem-based approach to management of marine areas. (January 2023) - Ruskule, Anda; Kotta, Jonne; Saha, Champa Rani; Arndt, Philipp; Ustups, Didzis; Strāķe, Solvita; Bergström, Lena
Abstract: The concept of Green Infrastructure (GI) can facilitate integration of ecological considerations and ecosystem service mapping into spatial planning. GI has been introduced in EU policy as a key tool for implementing the objectives of the EU Biodiversity Strategy 2020 on halting the loss of biodiversity as well as addressing other global environmental problems. Unlike terrestrial ecosystems, mapping of marine GI is still in infancy. Here, application of GI concept in mapping was developed and tested for a large marine region, the Baltic Sea, using existing regional spatial data sets on the distribution of different ecosystem components. Using a qualitative valuation approach, experts assessed 36 marine ecosystem components with respect to their relevance for six ecological value criteria and ten ecosystem services. Then, maps representing the ecological value of Baltic Sea ecosystems and their potential supply of ecosystem services were developed based on a hierarchical aggregation structure, designed to avoid double-counting of features that appeared in many data layers. Finally, results of the ecological value and ecosystem service supply mapping were integrated into the marine GI map. These pioneering results are used to discuss how marine GI mapping can support the ecosystem-based approach in MSP, by improving the knowledge base on the roles and connectedness of ecosystem components. Applied at the transboundary regional scale, as here, the GI concept can support cross-border coherence in spatial planning and provide practical management solutions to improve connectivity and functioning of MPA networks, or develop sustainable planning solutions of marine space. Highlights: A concept for marine green infrastructure mapping was developed. The systematic, data-driven approach was applied at the scale of a marine region. Results reveal areas of high ecological value and ecosystem service potential.